Some Studies in Hemirings by the Falling Fuzzy k-Ideals. (4th August 2021) - Anjum, R.; Sarfraz, F.; Kausar, N.; Gaba, Y. U.; Aydi, H.; Munir, M.; Salahuddin,
Abstract : In this article, we establish the idea of falling fuzzy k -ideals in hemirings through the falling shadow theory and fuzzy sets. We shall express the relations between fuzzy k -ideals and falling fuzzy k -ideals in hemirings. In particular, we shall establish different characterizations of k -hemiregular hemirings in the perfect positive correlation and independent probability space by means of falling fuzzy k -ideals.